The Numerical Class of a Surface on a Toric Manifold - Hiroshi Sato (International Journal of Mathematics and Mathematical Sciences)
In this paper, we give a method to describe the numerical class of a torus invariant surface on a projective toric manifold. As applications, we can classify toric 2-Fano manifolds of the Picard number 2 or of dimension at most 4.